Color Code –The Replacement for Bar Code - Neena George, P; Johnson, Silpa; Arif, PA; Pavitran, Naveen; Davis, Diana (International Journal of Computer Sciences and Engineering, 2014)
In our day-today life we come across a lot of situations where coding is needed. Coding is a technique that reduces the space to store the data. It also makes it easier for future access. During coding, the data in one form is coded to another form which may be legible and sometimes not. This happens because the form of representing the data gets changed while coding. The existing coding formats like barcode have been successful because of its application in several areas like health care and hospital settings, library services and coding of products by its manufacturer. There have been a lot advancement in sensor Technology which paves way to an efficient coding system. Color sensor Technology helps us to replace the existing Bar code system. In this paper, a new approach for coding is introduced by using color codes in place of bar codes. Data compression and encoding are done here to make color codes. Bar code scanner cannot read the code if it is crumpled or distorted and also the length increases the scanning time also increases accordingly. The color fading can be reduced by using colors of different intensities.